Decision Support System for Hiring Expert Staff at CV. BMS Using AHP Method - Yusuf Putra; Kanafi Kanafi; Mira Fitriana (Institut Teknologi Bisnis AAS Indonesia, 2023)
The selection process for expert employees must be managed properly because it will greatly affect the company'sperformance. Therefore, it is necessary to carry out a competency-based employee selection process to produce the best employeesand according to the needs of the company. The role of a decision support system will greatly assist managers in processing employeerecruitment selection data without compromising the assessment parameters set by a company. The selection process for hiringemployees manually, especially in the process of calculating the final value of each prospective employee, will take a lot of time,especially if the number of prospective employees participating in the selection is very large. In this study CV. Bangkit MandiriSejahtera (BMS) Semarang, a company engaged in the field of building contractors in Central Java, especially in the Semarang area,will apply the AHP (Analytical Hierarchy Process) method to the Decision Support System for hiring experts to get maximum results.